Intelligent design optimization of battery pack enclosure for electric vehicle by considering cold‐spraying as an additive manufacturing technology. Issue 3 (7th April 2020) - Pal, Santanu Kumar; Singh, Surinder; Singh, Harpreet; Le Phung, My Loan; Yooyen, Somaseak; Sleesongsom, Suwin
Abstract: Vibrations shocks induced during working conditions cause stresses and deformations of the battery case parts and heating may cause fire, which affects vehicle safety. Hence, the battery case and its parts should be of better mechanical features and lightweight to make the vehicle more efficient and safer. To achieve all the requirements, cold spraying found to be the potential technology for additive manufacturing the parts with better conductivities and lesser porosities as compared to the parts produced by conventional methods. Therefore, this article has proposed a consideration of the cold spray technology to improve the mechanical performances of the battery casing, including maximizing the minimum natural frequency, and minimizing the maximum deformation. ANSYS Workbench has been used for finite element modeling of battery pack enclosures. The model of the battery pack enclosures has been analyzed by obtaining the natural frequencies of the order 10. Further, static analysis has been performed to get the maximum deformation. Finally, a parametric model has been established and multiobjective optimization has been performed. The results obtained with the cold sprayed process show that the value of maximum deformation is being lowered by 59.49% and has a much higher value of natural frequency than that obtained with conventional methods.